2020
DOI: 10.1136/jnnp-2019-322725
|View full text |Cite
|
Sign up to set email alerts
|

New insights in post-traumatic headache with cluster headache phenotype: a cohort study

Abstract: ObjectivesTo define the characteristics of post-traumatic headache with cluster headache phenotype (PTH-CH) and to compare these characteristics with primary CH.MethodsA retrospective study was conducted of patients seen between 2007 and 2017 in a headache centre and diagnosed with PTH-CH that developed within 7 days of head trauma. A control cohort included 553 patients with primary CH without any history of trauma who attended the headache clinic during the same period. Data including demographics, attack ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Eight studies among the selected studies reported the prevalence of gender discrimination in CH patients [2,8,19,[24][25][26][27][28]. The selected studies from 2004 to 2021 demonstrate the predominance of males among CH patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies among the selected studies reported the prevalence of gender discrimination in CH patients [2,8,19,[24][25][26][27][28]. The selected studies from 2004 to 2021 demonstrate the predominance of males among CH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Head trauma and CH association was the least reported factor. Grangeon et al recently reported an extensive study on post-traumatic headache (PTH) in 553 CH patients [ 8 ]. This study revealed 26 patients with post-traumatic headache and linked this to the chronic and intractable CH form.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic TAC is reported following a head injury. 3 The suggested mechanism for post-traumatic migraine is secondary to axonal injury or a shearing effect of the brainstem, even after mild or moderate injury. A physiological shift within the brainstem can lead to chronic migraine.…”
Section: Hemicrania Continuamentioning
confidence: 99%
“…In 1 study of the largest series of PTH‐CH patients, PTH‐CH patients vs CH patients were more likely to suffer from chronic cluster, prominent autonomic features, as well as intractable and comorbid chronic migraine. Several theories have been proposed for post‐traumatic CH, including the release of inflammatory mediators, sensitization of pain pathways, and hypothalamic trauma with subsequent dysfunction 50 …”
Section: Cgrp and Ch Pathophysiologymentioning
confidence: 99%